Physico-Chemical Characterization and Product Development from 5 Cultivars of Phoenix dactylifera L. (Date) - Neela, Fatema Tuj Johora; Rahman, Md. Masuder; Akhter, Md. Shamim (European Journal of Scientific Exploration, 2019)
The thesis was carried out to determine the physico-chemical characteristics and to develop products from date (Phoenix dactylifera L.). The dates were of different varieties like Zardan, Khasab, Mariam, Barhi, Gounda and were purchased from Khulna region during August to November, 2018 and originating countries were Iran, Oman, Saudi Arabia, Tunisia. The experiment was laid out in Completely Randomized Design (CRD) with three replications. Best performance was showed by group no. 05 (cultivar: Gounda, origin country: Tunisia) in respect of the highest amount of total weight of fruit (10.925 g), seed weight of fruit (1.57 g) and weight of edible portion of fruit (9.369 g). Among the groups, highest fruit volume was (0.077 m3) and percentage of edible portion (90.848%) observed from group no. 01 (cultivar: Zardan, origin country: Iran). Highest fruit diameter (4.24 cm) found in group no. 03 (cultivar: Mariam, origin country: Saudi Arabia). The highest moisture content of fruit pulp (14.82 g/100g), vitamin C content of fruit pulp (0.99 mg/100g) and total phenol content of fruit pulp (5.144 mg/g) were observed from group no. 05. Group no. 03 showed the highest pH (6.8), TSS (10.5%). T-acidity (5.12%) showed by both 03 and 04 (cultivar: Barhi, origin country: Saudi Arabia) groups. Maximum anthocyanine 0.840 mg/100g found in group no. 04. The highest flavonoids content of fruit pulp was found in group no. 01 (8.664 g/100g). In case of development of product from date, jams were showed the highest shelf-life (15 days and 75 days) in both conditions (room temperature and refrigeration temperature) respectively. Date milk-shake was showed the lowest shelf-life (2 days and 7 days) in both conditions (room temperature and refrigeration temperature), respectively. Considering all the characteristics group no. 05 showed the best result among other groups. More studies are suggested to find out more nutritional values such as dietary fiber, ash, crude protein, carbohydrate, carotenoids, minerals and amino acids.